Do Peers Protect People or Put Them at Risk of Recidivism? Friendship Quality and Peer Crime Among Justice-Involved Youth - Confer, Leanne M. (Crime & delinquency, 2024)
Despite theoretical acknowledgments that peers can be either “good” or “bad” for criminal offending and recidivism, criminological research most often models peers as a criminogenic influence on offending behaviors. To explore the impact of peer relationships and to expand on theoretical conceptualization of peer relationship quality, the current study uses Pathways to Desistance data to examine the effects of peer quality and peer delinquency in recidivism over time among a sample of 1,272 individuals adjudicated during adolescence. Findings from a series of mixed-effects models demonstrate that peer quality is significantly predictive of increased aggressive offending. However, quality mitigates the relationship between peer delinquency and income offending, highlighting a need for further research considering potential protective aspects of peer relationships.